1990
DOI: 10.1007/bf00007786
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of grain size correction procedures for organic micropollutants and heavy metals in marine sediments

Abstract: Four grain size correction procedures were tested for their applicability for comparing concentrations of heavy metals and organic micropollutants (PCBs, PAHs) in sediments . A simple and straightforward procedure proved best : wet sieving of fresh sediment, isolating and analysing the < 63 ,um grain size fraction and expressing the pollutant concentration as a proportion of the fraction's dry weight . The total analytical errors, expressed as the variation coefficient of the average concentrations, were 3 .8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 12 publications
2
32
0
2
Order By: Relevance
“…For instance, generally, the finer a sediment the greater its concentration of both natural and anthropogenic pollutants (e.g. its trace metal concentration Salomons and Forstner, 1980;Thorne and Nickless, 1981;Loring, 1990), radionuclide content (Aston et al, 1985;Bonnett et al, 1988;Oldfield et al, 1993;Clifton et al, 1997Clifton et al, , 1999McCubbin et al, 2000) or polychlorinated biphenyls (PCBs) quantity (Klamer et al, 1990;Camacho-Ibar and McEvoy, 1996). Typically, this is due to finer grained sediments possessing larger specific surface areas, surface charges and cation exchange capacities, which enhance the extent of their preferential chemical adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, generally, the finer a sediment the greater its concentration of both natural and anthropogenic pollutants (e.g. its trace metal concentration Salomons and Forstner, 1980;Thorne and Nickless, 1981;Loring, 1990), radionuclide content (Aston et al, 1985;Bonnett et al, 1988;Oldfield et al, 1993;Clifton et al, 1997Clifton et al, , 1999McCubbin et al, 2000) or polychlorinated biphenyls (PCBs) quantity (Klamer et al, 1990;Camacho-Ibar and McEvoy, 1996). Typically, this is due to finer grained sediments possessing larger specific surface areas, surface charges and cation exchange capacities, which enhance the extent of their preferential chemical adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Popular approaches tend to normalise data either relative to the abundance of a specific particle size interval class or to carry out their analyses on a specifically separated particle size fraction (e.g. b16 Am (Klamer et al, 1990), b20 Am (Ackermann, 1980;Ackermann et al, 1983;Christiansen et al, 2002), b63 Am Araujo et al, 1988;Klamer et al, 1990), b100 Am (Langston, 1986), b150 Am (Jones and Turki, 1997), b250 Am (Hornung et al, 1989)). Although these methods can be considered reliable and advantageous, they require additional and, in the latter case, time-consuming laboratory work.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in numerous studies that hydrocarbon concentrations peak in the silt/clay fractions (including MHW, Little et al 1987). Klamer et al (1990) demonstrated the importance of grain size variations in assessment of PAHs and metals concentrations in sediments. Work on polluted urban soils shows that sorption strength of persistent organic pollutants peaks in silts (PAHs) and clays (PCBs), but that the very high TOC-water partition coefficients effectively sequester the pollutant reducing its bioavailability (Krauss and Wilcke 2002).…”
Section: Visual Evidence Of Physical Processesmentioning
confidence: 98%
“…Soil contamination by heavy metals (Wilcke et al 1998), radionuclides (van der Perk et al 2000) or persistent organic pollutants, such as polycyclic aromatic hydrocarbons (PAHs) (Maliszewska-Kordybach 1996) and polychlorinated biphenyls (PCBs) (Klamer et al 1990) are important public health concerns (Rowat 1999;Roos et al 2004). Assessment of the extent and severity of soil contamination requires thorough investigation before remediation can proceed (Manz et al 1999;Zhu and Shaw 2000), but soil-related analytical data can be strongly affected by particle size effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary, therefore, to first remove this influence by either normalizing data relative to the abundance of a specific particle size interval or fractionating samples into specific sizes (e.g. <16 µm (Klamer et al 1990), <20 µm (Ackermann et al 1983), <50 µm (Aston and Stanner 1982), <60 µm (Ackermann 1980), <63 µm (Araujo et al 1988;), <75 µm (Clifton and Hamilton 1982), <100 µm (Langston 1986), <150 µm (Jones and Turki 1997), <250 µm (Hornung et al 1989). Although these methods can be considered reliable and advantageous, they require additional and, in the case of fractionating samples into specific size ranges, time-consuming laboratory work.…”
Section: Introductionmentioning
confidence: 99%